PENGARUH MEDIA EXPOSURE, GOOD CORPORATE GOVERNANCE, DAN SERTIFIKASI LINGKUNGAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Angelisa Martha Tiur Tambun (2022)
The purpose of this study is to analyze whether media exposure, environmental certification, audit committee, and the board of commissioners have an influence on the disclosure of corporate social responsibility. This study uses quantitative methods with secondary data done on non-financial companies listed on the Indonesia Stock Exchange in 2017-2020 by analyzing annual reports and company sustainability reports. The sampling method used is purposive sampling with certain criteria. The results of this study indicate that the media exposure and audit committee variables have a significant influence on the disclosure of corporate social responsibility. In contrast to the environmental certification variable and the board of commissioners which show no significant effect on the disclosure of corporate social responsibility. Keywords: Corporate Social Responsibility, Media Exposure, Environmental Certification, Audit Committee, and Board of Commissioners.